Hydrogen sulfide alleviates lipopolysaccharide-induced myocardial injury through TLR4-NLRP3 pathway - Xia, Yuxuan; Zhang, Wenya; He, Kaichuan; Bai, Lu; Miao, Yuxin; Liu, Biyu; Zhang, Xiangjian; Jin, Sheng; Wu, Yuming (Physiological research, 2023)
To investigate the effect of hydrogen sulfide (H2S) on myocardial injury in sepsis-induced myocardial dysfunction (SIMD), male C57BL/6 mice were intraperitoneally injected with lipopolysaccharide (LPS) (10 mg/kg, i.p.) to induce cardiac dysfunction without or with the H2S donor sodium hydrosulfide (NaHS) (50 μmol/kg, i.p.) administration 3 h after LPS injection. Six hours after the LPS injection, echocardiography, cardiac hematoxylin and eosin (HE) staining, myocardial damage and inflammatory biomarkers and Western blot results were analyzed. In mice, the administration of LPS decreased left ventricular ejection fraction (LVEF) by 30 % along with lowered H2S levels (35 % reduction). It was observed that cardiac troponin I (cTnI), tumor necrosis factor-alpha (TNF-alpha), and interleukin-1beta (IL-1beta) levels were all increased (by 0.22-fold, 2000-fold and 0.66-fold respectively). HE staining revealed structural damage and inflammatory cell infiltration in the myocardial tissue after LPS administration. Moreover, after 6 h of LPS treatment, toll-like receptor 4 (TLR4) and nod-like receptor protein 3 (NLRP3) expressions were up-regulated 2.7-fold and 1.6-fold respectively. When compared to the septic mice, NaHS enhanced ventricular function (by 0.19-fold), decreased cTnI, TNF-alpha, and IL-1beta levels (by 11 %, 33 %, and 16 % respectively) and downregulated TLR4 and NLRP3 expressions (by 64 % and 31 % respectively). Furthermore, NaHS did not further improve cardiac function and inflammation in TLR4-/- mice or mice in which NLRP3 activation was inhibited by MCC950, after LPS injection. In conclusion, these findings imply that decreased endogenous H2S promotes the progression of SIMD, whereas exogenous H2S alleviates SIMD by inhibiting inflammation via the TLR4-NLRP3 pathway suppression.
Keywords: Stroke Volume; Animals; zánět; Heart Injuries; lipopolysacharidy; sulfan; Tumor Necrosis Factor-alpha; toll-like receptor 4; sepse; Sepsis; funkce levé komory srdeční; kardiomyopatie; Mice; Lipopolysaccharides; myši; NLR Family, Pyrin Domain-Containing 3 Protein; Inflammation; TNF-alfa; Hydrogen Sulfide; protein NLRP3; Male; Toll-Like Receptor 4; tepový objem; poranění srdce; Cardiomyopathies; zvířata; mužské pohlaví; Mice, Inbred C57BL; Ventricular Function, Left; myši inbrední C57BL